2007
DOI: 10.1016/j.neuron.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Synapse-Specific and Developmentally Regulated Targeting of AMPA Receptors by a Family of MAGUK Scaffolding Proteins

Abstract: In our paper we incorrectly listed CTCTATTGTTCGACTGTATAT as an alternative PSD-93 shRNA targeting sequence. The correct alternative sequence is CTGTGAGATTTGTAGCAGAAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 0 publications
2
57
1
Order By: Relevance
“…30 Synaptic transmission can also be modulated trans-synaptically, as in the case of the pre-synaptic adhesion molecule Neurexin-3 (encoded by the mouse orthologue of NRXN3), which can control the post-synaptic expression of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) glutamate receptors in the hippocampus. 31 All of these proteins are essential during the formation and maturation of synapses [Erbin, 32 Postsynaptic density (PSD)-93/ chapsyn-110, 33 Neurexin-3 34 ]. This evidence accrues on a robust body of evidence implicating synaptic function in ID and ASD pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…30 Synaptic transmission can also be modulated trans-synaptically, as in the case of the pre-synaptic adhesion molecule Neurexin-3 (encoded by the mouse orthologue of NRXN3), which can control the post-synaptic expression of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) glutamate receptors in the hippocampus. 31 All of these proteins are essential during the formation and maturation of synapses [Erbin, 32 Postsynaptic density (PSD)-93/ chapsyn-110, 33 Neurexin-3 34 ]. This evidence accrues on a robust body of evidence implicating synaptic function in ID and ASD pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is considerable functional overlap between the different PSD-MAGUKs. PSD93 and PSD95, for example, play similar roles supporting basal synaptic transmission in the hippocampus, but in largely non-overlapping populations of synapses (Elias et al, 2006). Additionally, expression of SAP102 is upregulated in the absence of PSD93 and PSD95, indicating a possible compensatory mechanism (Elias et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because PSD93 is closely related to PSD95 (Brenman et al, 1996;Kim et al, 1996), and may be the principle MAGUK at a subset of hippocampal synapses (Elias et al, 2006), we reasoned that PSD93 might play the primary role in stabilizing new spines. We therefore measured the PSD93-GFP content as new spines matured on dendrites of hippocampal pyramidal neurons co-transfected with PSD93-GFP and DsRed-Express.…”
Section: New Spines Have Even Lower Levels Of Psd93-gfp But Accumulamentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of miR-142-5p inhibition in Aβ 42 -treated SH-SY5Y cells was investigated with the evaluation of PSD-95 expression. A loss of synaptic integrity leads to cognitive impairment in the AD brain (Coleman and Yao, 2003; Gylys et al, 2004), and PSD-95 as a neuronal scaffolding protein (Niethammer et al, 1996) is known to influence synapse maturation and regulate synaptic plasticity in the neuronal network (Kennedy, 2000; Elias et al, 2006). Several studies demonstrated that the level of PSD-95 was considerably reduced in the AD brain (Gylys et al, 2004; Love et al, 2006).…”
Section: Resultsmentioning
confidence: 99%